Стихотворения и поэмы ["Перевал" и "Чегемская поэма"] - Кулиев Кайсын Шуваевич (1970)
Экземпляры: КХ (20210319) / Инвентарный номер: 510503 / Сис.шифр: С(Балк) / Авт.знак: К 90 / ГРНТИ: 17 / ББК: 84(2=632.93)-5